2023
DOI: 10.3390/ijms241814028
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling in Insect Development: A Simple Pathway with Diverse Functions

Yao Chen,
Haomiao Li,
Tian-Ci Yi
et al.

Abstract: Notch signaling is an evolutionarily conserved pathway which functions between adjacent cells to establish their distinct identities. Despite operating in a simple mechanism, Notch signaling plays remarkably diverse roles in development to regulate cell fate determination, organ growth and tissue patterning. While initially discovered and characterized in the model insect Drosophila melanogaster, recent studies across various insect species have revealed the broad involvement of Notch signaling in shaping inse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 358 publications
0
3
0
Order By: Relevance
“…At first glance, the extreme versatility and pleiotropy of Notch signaling seems to make the task of reconstructing an evolutionary history of its involvement in metazoan development rather daunting. Although many reviews have summarized the function of Notch from different perspectives, there are still many areas where the function of Notch components is not well understood [ 3 , 10 ]. This review summarizes the past and present studies that have revealed some of the mechanisms underlying Notch signaling in invertebrate neurodevelopment and regeneration by using a few relatively typical species [ 44 , 52 , 245 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first glance, the extreme versatility and pleiotropy of Notch signaling seems to make the task of reconstructing an evolutionary history of its involvement in metazoan development rather daunting. Although many reviews have summarized the function of Notch from different perspectives, there are still many areas where the function of Notch components is not well understood [ 3 , 10 ]. This review summarizes the past and present studies that have revealed some of the mechanisms underlying Notch signaling in invertebrate neurodevelopment and regeneration by using a few relatively typical species [ 44 , 52 , 245 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Notch receptor is irreversible because it involves a proteolysis-mediated release of the Notch intracellular domain (NICD), which translocates to the nucleus and associates with a DNA-bound protein. Three primary modes of Notch actions have been discovered: lateral inhibition, boundary induction, and lineage decision [ 3 ]. Although each Notch molecule only signals once without being amplified by secondary messengers, Notch signaling is surprisingly robust in most tissues [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it also suggested that circRNAs can regulate the same pathway in different regulatory ways (regulating the transcription of parental genes and ceRNA mechanism). Insect Notch signaling plays remarkably diverse roles in development to regulate cell fate determination, organ growth and tissue patterning ( Chen Y. et al, 2023 ). And the Notch signaling plays essential roles during ovary development ( Shcherbata et al, 2004 ), leg growth ( Cordoba and Estella, 2020 ), and wing development ( Blair, 2007 ) in Drosophila melanogaster .…”
Section: Discussionmentioning
confidence: 99%